Meniscal Radial Tears: A Classification System Based on Tear Morphology - Jorge Chahla, M.D., Ph.D.; Derrick M. Knapik, M.D.; Harkirat Jawanda, B.S.; Felicitas Allende, M.D.; Horacio Rivarola, M.D.; Johnathon R. McCormick, M.D.; Robert F. LaPrade, M.D., Ph.D.; Garrett R. Jackson, M.D. (Arthroscopy Techniques, 2024)
Appropriate management of radial meniscal tears is complex, with continued efforts focused on optimizing diagnostic methods for identification to help dictate treatment, especially as surgical indications for repair have expanded, coupled with improvements in surgical techniques and instrumentation. Currently, no standardized classification system for radial meniscal tears exists, limiting the ability to accurately characterize injury patterns and guide surgical decision-making.